La Subversion du Personnage Romanesque dans le Roman "Le Village de L’allemand" de Boualem Sansal - Ahmed, Reda Saiah (جامعة وهران 2 محمد بن أحمد - كلية اللغات الأجنبية, 2021)
Our study focuses on the subversion of the traditional notion of the character through his vision of the world which is omnipresent in the novel Le village de l'allemand by Boualem Sansal. With this in mind, we immersed ourselves in the socio-historical aspect of the character, where we emphasized that Spatio-temporal clues build the novel while writing strategies manifest their factuality. By referring to the actual toponymies that constitute the novel structure, the author places his narrative de facto in the interdependence of the realistic novel. Indeed, the author deliberately inserts throughout the story a temporality evoking or even provoking a fiction-reality (con) fusion, this subversion manifests itself both at the thematic and scriptural level. At the end of this reflection, we concluded that this intermediary of history and memory manifests an intimately linked history of conflict.
Keywords: الأدب الواقعي -- الذاكرة الاجتماعية -- السرد الروائي -- الاستراتيجيات الكتابية -- رواية "قرية العلمين" -- النقد الأدبي